(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This paper examines the role and status of English in Sierra Leone. It examines the evolution of the Language in English and make a case for a national language .It examines the role of he Language in the Global stage and how that can be linked to Sierra Leone national development. It is the de-jure official language in the country. The 1991 Constitution of Sierra Leone, Act No. 6 which is the countrys grundnorm provides for it as official language. No indigenous language in Sierra Leone can better serve the function of togetherness and unity more than English language due to Sierra Leone political Polarization. It has our glorious past as it was brought to us by our colonial masters through colonialism who equally were not original owners of the language but they made it as theirs and they are still using it at their convenience. From the time of British colonization till today, English is the language used for all purpose-politics, education, media, diplomacy et al. No language can replace English as either official language or medium of communication. We cannot have a de facto national language because there is no one language that is used by majority of the population as their mother tongue. Sierra Leone needs a de jure national language for togetherness and unity which English can better serve that role. This can be done through human intervention that dictates which language(s) should be granted the status of National language for political reason and not linguistic reason through language policy and language planning.